Предмет: Математика,
автор: mariyayakovleva55
(3х-2)х²-2х(3х-2)+8(-3х)=0
(х+1)(х²+х+1)(х-1)=28
Ответы
Автор ответа:
0
(3x-2)^2-2x(3x-2)+8(-3x)=0
3x^3-2x^2-6x^2+4x-24x=0
3x^3-8x^2-20x=0
x(3x62-8x-20)=0
x1=0
D=64-4*3*(-20)=304=16*19
x2=(8+V(16*19))/6=4/3+(2V19)/3
x3=(8-V(16*19))/6=4/3-(2V19)/3)
второе подумаю
3x^3-2x^2-6x^2+4x-24x=0
3x^3-8x^2-20x=0
x(3x62-8x-20)=0
x1=0
D=64-4*3*(-20)=304=16*19
x2=(8+V(16*19))/6=4/3+(2V19)/3
x3=(8-V(16*19))/6=4/3-(2V19)/3)
второе подумаю
Похожие вопросы
Предмет: Другие предметы,
автор: abdayesena
Предмет: Математика,
автор: skerimova1111
Предмет: Математика,
автор: urobiya20000
Предмет: Математика,
автор: savka2003nk
Предмет: Литература,
автор: Аноним